Developmental Origins and Nephron Endowment in Hypertension - Gurusinghe, Shari; Tambay, Anita; Sethna, Christine B. (Frontiers in Pediatrics, 2017)
Primary hypertension continues to be one of the main risk factors for cardiovascular disease worldwide. A stable intrauterine environment is critical for the future development and health of the fetus. The developing kidney has been found to be especially vulnerable during this time period and epidemiological studies have demonstrated that an adverse in utero environment is associated with an increase risk of hypertension and chronic kidney disease. Macro- and micronutrient deficiencies as well as exposure to tobacco, alcohol and certain medications during gestation have been shown to negatively impact nephrogenesis and reduce one’s nephron number. In 1988, Brenner et al. put forth the controversial hypothesis that a reduced nephron complement is a risk factor for hypertension and chronic kidney disease in adulthood. Since then numerous animal and human studies have confirmed this relationship demonstrating that there is an inverse association between blood pressure and nephron number. As our understanding of the developmental programming of hypertension and other non-communicable diseases improves, more effective preventive health measures can be developed in the future.